The gendered occupational value of a U.S. education for skilled Indian immigrants. (27th January 2022) - Jacobs, Elizabeth; Kreisberg, A. Nicole
Abstract: This article revisits conventional understandings of gender differences in occupational attainment through the context of highly skilled legal migration in the United States. Drawing on a unique combination of nationally representative survey data of Indian lawful permanent residents and in‐depth interviews with skilled Indian migrants holding employer‐sponsored visas, we find that a U.S. education has a large premium in occupational prestige scores in the global labour market and has the power to mitigate the gender gap in immigrant occupational attainment. U.S. credentials, social networks, and mentorship programs help drive the occupational prestige‐generating function of a U.S. education for highly skilled Indian immigrant women. This article demonstrates aggregate occupational patterns among a nationally representative sample of Indian permanent residents and develops an in‐depth understanding of the process of occupational attainment. Our findings offer new insights into factors that mitigate gender inequality in the high‐skilled immigrant labour force.